Antonio Sánchez Barbudo, Estudios sobre Unamuno y Machado. Ediciones Guadarrama, Madrid, 1959; 326 pp. - Earle, Peter (El Colegio de México, 1960)
Se reseñó el libro: Estudios sobre Unamuno y Machado.